POWER RELATION BETWEEN TAREKAT QADIRIYAH WA NAQSYABANDIYAH (TAREKAT CUKIR) AND PARTAI PERSATUAN PEMBANGUNAN (PPP) IN JOMBANG, EAST JAVA - Al Abza, M Thohar; Kamsi, Kamsi Kamsi; Ismail, Nawari (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
Tarekat teaches its followers not to glorify conglomerates, to keep their distance from leader, and to live in a way of zuhud, including in the matters of politics. But the Tarekat Qadiriyah wa Naqsyabandiyah in Cukir Jombang was actually involved in practical politics as a supporter of Partai Persatuan Pembangunan (PPP). This paper, which was written in the form of ethnographic design according to the concept of the power relations of Foucault to find new perspectives about the actions of Tarekat communities in politics, in this case explaining the pattern of relations that occurred between the Tarekat Cukir and PPP and discovering the factors causing Tarekat Cukir to support PPP. This paper concludes that between Tarekat Cukir and PPP, there is a mutually beneficial pattern of relations in terms of proximity, but in terms of economic politics, the Tarekat Cukir feels disadvantaged. The dominant reason the Tarekat Cukir supports PPP is because of the dependence of Santri on their Mursyid who is a PPP politician. This is reinforced by the history between the two parties and the spiritual ties that connect the teachers who are both PPP politicians and Santris.